2021
DOI: 10.1007/s40615-020-00948-8
|View full text |Cite
|
Sign up to set email alerts
|

Structural Racism and COVID-19 in the USA: a County-Level Empirical Analysis

Abstract: Substantial health disparities exist across race/ethnicity in the USA, with Black Americans often most affected. The current COVID-19 pandemic is no different. While there have been ample studies describing racial disparities in COVID-19 outcomes, relatively few have established an empirical link between these disparities and structural racism. Such empirical analyses are critically important to help defuse "victim-blaming" narratives about why minority communities have been badly hit by COVID-19. In this pape… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
107
1
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(117 citation statements)
references
References 49 publications
4
107
1
1
Order By: Relevance
“…The disparate findings by race and ethnicity in our study are not novel in isolation; however, the persistence despite controlling for proposed inequity drivers highlights a concerning and enduring healthcare crisis. Furthermore, it supports concerns 12,25,45 that other unidentified confounders (i.e., structural racism, testing, etc.) drive the association.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…The disparate findings by race and ethnicity in our study are not novel in isolation; however, the persistence despite controlling for proposed inequity drivers highlights a concerning and enduring healthcare crisis. Furthermore, it supports concerns 12,25,45 that other unidentified confounders (i.e., structural racism, testing, etc.) drive the association.…”
Section: Discussionmentioning
confidence: 60%
“…7 The etiology of health disparities is multifactorial and includes differences in sociocultural environment, behavior, biological profile, healthcare system, and clinical events. [8][9][10][11][12][13][14][15][16][17][18] Specific to COVID-19, multiple explanations driving health disparities have been proposed, for example, higher rates of "essential workers," multigenerational housing, increased rates of poverty, comorbidities, and uninsured status in minority populations. 19 Early data regarding COVID-19's impact on health disparities are emerging; [20][21][22][23][24][25][26][27][28][29] studies rarely account for multiple socioeconomic variables and granular patient-level characteristics simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…With national age-adjusted death rates revealing an even more profound racial disparity in COVID-19 mortality, it is even more crucial to determine the reasons for these disparities. Although many papers have suggested that structural racism is a critical factor in explaining racial disparities in COVID-19 mortality, we are aware of only six that have demonstrated this relationship empirically by explicitly measuring structural racism [42][43][44][45][46][47]. Tan et al [42] examined the relationship between four measures of structural racism (residential segregation and differences in incarceration rates, economic status, and employment status) and county-level COVID-19 death rates, finding that the degree of residential segregation was significantly related to higher overall death rates.…”
Section: Introductionmentioning
confidence: 90%
“…5 Since COVID-19 burden is often greater in socioeconomically disadvantaged communities, in-person instruction has been unavailable or inconsistent for the students who may need it the most, thereby increasing educational disparities for children in lower income families, communities of color, and/or households that include essential workers, contain multiple generations, experience crowded housing, and with members who have high-risk chronic conditions (e.g., hypertension, diabetes, obesity). 6,7 Yet uncertainty surrounding infectiousness and management of pre-and asymptomatic populations has slowed school re-opening in the U.S. Resuming in-person instruction during the pandemic requires bringing susceptible children and adults into a congregate setting for extended periods of time with daily return into their communities. Recent studies suggest that secondary infection risk in schools is low when basic precautions are followed.…”
Section: Introductionmentioning
confidence: 99%
“…5 Since COVID-19 burden is often greater in socioeconomically disadvantaged communities, in-person instruction has been unavailable or inconsistent for the students who may need it the most, thereby increasing educational disparities for children in lower income families, communities of color, and/or households that include essential workers, contain multiple generations, experience crowded housing, and with members who have high-risk chronic conditions (e.g., hypertension, diabetes, obesity). 6,7…”
Section: Introductionmentioning
confidence: 99%